The genus Pemphredon Latreille (Hymenoptera: Crabronidae) from China, with description of a new species. (3rd April 2021) - Bashir, Nawaz Haider; Ma, Li; Li, Qiang
ABSTRACT: Pemphredon rugidorsalis: Bashir and Ma, sp. nov ., of the family Crabronidae, is described from the Palearctic region of China. An identification key to the species of the genus Pemphredon from China is provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:A4B5CAE9-C156-4EF2-9BB0-2A56FD7396F7